Association of P16 Expression with Clinicopathological Features of Oral Cavity Squamous Cell Carcinoma Patients in Bali - Ampur, O. Y.; Sudarsa, I Wayan; Suryawisesa, Ida Bagus (BALI MEDICAL JOURNAL, 2016)
Background: Oral cavity cancer is considered as a major health problem worldwide and has been associated with high recurrence rate and poor prognosis. Oral cavity squamous cell carcinoma (OCSCC) in Sanglah General Hospital Denpasar contributed to 71.7% of all head and neck cancer from 2002-2011 with an increasing trend annually. Advances in our understanding of OCSCC have not improved the outcome in OCSCC management significantly. Therefore, many studies have focused on the roles of biomolecular markers in OCSCC. One of biomolecular marker that has been the focus of many OCSCC studies is p16. Method: This was an analytic cross sectional study with 31 samples to determine the association of p16 expression with age group, tumor location, stage, and grade in OCSCC. Data was analyzed descriptively and the association between variables were evaluated with Chi-Square or Fisher’s Exact Test with a p value <0.05 was considered significant. Results: From 31 samples collected, the mean age was 56.19±15.197 years old. 17 samples (54.8%) were female and 17 samples (54.8%) were from the ?60 years old age group. Majority of the tumor was located on the tongue (14 samples; 45.2%) with postero-inferior group location (19 samples; 61.3%). Almost half of the samples were in Stage IVA-B (15 samples; 48.4%) and within high grade group (24 samples; 77.4%) meanwhile 21 samples (67.7%) were in low p16 expression group. There was a significant association between p16 expression with tumor grade group (p=0,044). Conclusion: p16 expression was significantly associated with tumor grade in OCSCC patients.
Keywords: Oral Cavity Squamous Cell Carcinoma, p16, clinicopathological features.